2018
DOI: 10.1016/j.aninu.2018.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Dietary L-theanine alleviated lipopolysaccharide-induced immunological stress in yellow-feathered broilers

Abstract: L-theanine, a natural nonprotein amino acid with a high biological activity, is reported to exert anti-stress properties. An experiment with a 3 × 2 factorial arrangement was conducted to investigate the effects of dietary L-theanine on growth performance and immune function in lipopolysaccharide (LPS)-challenged broilers. A total of 432 one-day-old male yellow-feathered broilers were randomly assigned to 3 dietary treatments (control, antibiotic and L-theanine diets) with 2 subgroups of each (6 replicate cage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…This effect has already been observed in other studies with broilers and is dependent on the LPS dose, number of applications, and time between application and weighing of the birds. For example, Li et al (2018), after applying 0.6 mg of LPS/kg of BW at 24, 25, and 26 days of age, observed a reduction of 15.4% in feed intake and of 16.2% in weight gain in the period of 22 to 28 days of age. Zhang et al (2020) observed that 24 h after the application of 5.0 mg of LPS/kg of BW at 21 days of age resulted in a 44.6% reduction in weight gain compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect has already been observed in other studies with broilers and is dependent on the LPS dose, number of applications, and time between application and weighing of the birds. For example, Li et al (2018), after applying 0.6 mg of LPS/kg of BW at 24, 25, and 26 days of age, observed a reduction of 15.4% in feed intake and of 16.2% in weight gain in the period of 22 to 28 days of age. Zhang et al (2020) observed that 24 h after the application of 5.0 mg of LPS/kg of BW at 21 days of age resulted in a 44.6% reduction in weight gain compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by changes in the partitioning of nutrients away from growth and toward processes associated with the acute-phase response. Lipopolysaccharide is a molecule present in the outer membrane of gramnegative bacteria and has commonly been used to induce an inflammatory response in broilers in experimental conditions (Lieboldt et al, 2017;Li et al, 2018;Zhang et al, 2020). Lipopolysaccharide injections induce the synthesis and release of pro-inflammatory cytokines such as tumor necrosis factor-α, interleukin-1β (IL-1β), and IL-6 (Yang et al, 2008), which activate neutrophils, monocytes, and macrophages to initiate killing of bacteria and tumor cells and stimulate T and B lymphocyte proliferation (Calder, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…LPS induction in vivo stimulated monocyte‐macrophage cell synthesis and resulted in the release of a large number of proinflammatory cytokines, such as IL‐1β, IL‐6 and TNF‐α, which promote metabolism and increase nutrient consumption, thereby resulting in the inhibition of animal growth and tissue damage (Li et al, ). In the immune system, proinflammatory cytokines are major cellular messengers, regulating the body's innate and adaptive immune response to antigens and infectious agents.…”
Section: Discussionmentioning
confidence: 99%
“…Igs are glycoproteins and one of the vital components of the immune system and previous reports suggested a beneficial role of Igs in inflammatory response (Brimelow et al, 2015; Elluru et al, 2015; Li et al, 2018). In this study, we found that IgG involves in colonic colitis as TNBS significantly inhibited serum IgG production.…”
Section: Discussionmentioning
confidence: 99%